Antimicrobial Activity of Lactobacillus plantarum Strains Isolated from Fermented Olives Origin - MR Fazeli; E Vaghari; H Jamalifar; Z Ebrahim; N Samadi (Institue of Medicinal Plants, ACECR, 2009)
Background: Lactobacillus plantarum isolated from fermented olives has been extensively studied with the aim of its use in starter cultures for olive or other production fermentations, but little is known about its antimicrobial resistance and its probiotic effects. Objectives: The aim of this study was to determine the antimicrobial activity using different strains of L. plantarum isolated from fermented olives origin against Salmonella typhimurium. Methods: Three strains of L. plantarum were isolated from fermented green olives (Lp1,Lp2,Lp3).they were grown in MRS broth at 37o C. Overnight culture of S. typhimurium was added to MRS broth containing 108 CFU/mL of L. plantarum. Reduction of the viable cells was assayed on bismuth sulfit agar medium for 24h. Antimicrobial activities of L. plantarum cells against the test strain of Salmonella were also determined by measuring the diameter of growth inhibition zone in agar spot test. Results: All of the L. plantarum strains could inhibit growth of S. typhimurium. Also visible inhibition zones were observed around the spotted cells of L. plantarum strains in the spot tests. Conclusion: Results showed great inhibitory effect of the L. plantarum strains against Salmonella and were differed in their antimicrobial activities which could be due to the metabolite secreted by the L. plantarum strains specially type of bacteriocins.